EKSPLORASI ETNOMATEMATIKA DALAM ALAT MUSIK XYLOPHONE PADA PEMBELAJARAN MATERI KELIPATAN PERSEKUTUAN TERKECIL (KPK) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA - Tyaningsih, Ratna Yulis; Hayati, Laila; Utama, Raden Septiaji Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Mathematics is more than just numbers and formulas; it's ingrained in society and daily existence. Learning becomes more engaging and enjoyable when cultural components are incorporated into mathematical ideas. In order to enhance learning outcomes and student motivation, this study intends to investigate the concept of ethnomathematics on the Xylophone musical instrument and its use in learning Least Common Multiples (LCM). This kind of research uses an exploratory research methodology and is qualitative. Developing a conceptual framework, formulating the research topic, identifying the study subject, developing instruments, gathering and evaluating data, and drawing conclusions are the steps involved in conducting research. Students of SD Negeri 35 Ampenan in Grade 5 served as the research subjects. The study's conclusions demonstrate how using the xylophone as a musical instrument while studying LCM content has a big impact on students' motivation and learning outcomes. This is seen by the 23.3% improvement in student learning outcomes and the learning motivation score, which is in the High category with an average of 4.16. In order to enhance learning objectives and student motivation, educators must investigate additional cultural components as learning innovations.